A-307 Relationship Between Nonverbal Measure of Intelligence and Achievement Performance in Rural, Latinx Youth. (17th August 2022) - McMillen, Taylor; Young, Krysta; Carlson, Katherine; Hamilton, Elizabeth
Abstract: Objective: This study examines the relationship between the Wechsler Nonverbal Scale of Ability (WNV) and achievement in rural Latinx youth. Although concurrent validity for the WNV with other intelligence measures is established, there is sparse research on its association with academic performance. Methods: Participants (n=15) were Latinx youth, ages 8 to 17 years, including nine males and six females. Participants were administered the WNV and the Woodcock-Johnson IV Tests of Achievement (WJ-IV-ACH) as part of a psychoeducational battery. The WNV minimizes cultural/linguistic factors, providing a Full Scale score and four subtests: 1) Matrices, 2) Coding, 3) Spatial Span, and 4) Picture Arrangement. The WJ-IV-ACH includes Broad Achievement and academic cluster scores. Correlations analyzed relationships between WNV and WJ-IV-ACH scores. Results: A moderate correlation was found between WNV Full Scale and Broad Achievement (r= .44). Matrices and Picture Arrangement were moderately related to Broad Achievement (r= .39, r= .39). Matrices was strongly correlated to reading fluency (r= .60), and moderately correlated to broad reading (r= .39) and math problem solving (r= .34). Coding was associated with math calculation (r= .48). Spatial Span was strongly correlated with math problem solving (r=.53) and linked to math calculation (r= .48). Picture Arrangement was moderately correlated with broad reading, reading comprehension, math problem solving, and written expression (r= .37, r= .31, r= .33, r= .30). Conclusion: Despite the small sample size, results suggest that a diversity-informed measure of intellectual ability is related to youth's broad achievement scores. Additionally, WNV subtest scores are differentially associated with academic domains.